Tracing the invertebrate herpesviruses in the global sequence datasets - Rosani, Umberto; Gaia, Morgan; Delmont, Tom O.; Krupovic, Mart (Frontiers in Marine Science, 2023)
The family of Malacoherpesviridae is currently represented by only two viruses infecting molluscs, Ostreid herpesvirus 1 (OsHV-1) and Haliotid herpesvirus 1 (HaHV-1), both causing detrimental infections in aquaculture species. Malacoherpesvirus-like sequences were also detected through genome sequencing projects in amphioxus (Branchiostoma species) and annelid worm (Capitella teleta), suggesting the existence of a hidden diversity of malacoherpesviruses in aquatic animals. Here, to extend the knowledge on malacoherpesvirus diversity, we searched for the presence of malacoherpesvirus relatives in genomic, transcriptomic and metagenomic datasets, including from the Tara Oceans expedition, and report 4 novel malacoherpesvirus-like genomes (MalacoHV1-4). Genomic analysis suggested gastropods and bivalves as the most probable hosts for these new malacoherpesviruses. Phylogenetic analysis based on the family B DNA polymerase placed the novel MalacoHV1 and MalacoHV3 as sister lineages of OsHV-1 and HaHV-1, respectively, whereas MalacoHV2 and MalacoHV4 showed higher divergence. The viral genome found associated with amphioxus together with MalacoHV4 formed a sister clade to the mollusc and annelid malacoherpesviruses, suggesting an early divergence of the two virus assemblages. In conclusion, although relatively rare in the available sequence databases, the previously undescribed malacoherpesviruses, MalacoHV1-4, circulate in aquatic ecosystems and should be considered as possible emerging viruses under changing environmental conditions.